Comparative Analysis of the Representation of Social Values in Russian, English and Uzbek Proverbs - Mubina Olimovna Nosirova (Goodwood Publishing, 2026)
Purpose: This study aims to compare the representation of social values in Russian, English, and Uzbek proverbs, identifying both universal and culture-specific features of social values in these languages. Research Methodology: The research employs comparative, linguacultural, and semantic analysis methods, with contextual interpretation. The study analyzes proverbs related to values such as labor, family, honesty, collectivism, and individualism from corpus and lexicographic sources. Results: The study found that while universal values are present in all three languages, their interpretation and emphasis differ across cultural and historical contexts. Russian proverbs focus on collectivism and moral-ethical values, English proverbs emphasize individualism and pragmatism, and Uzbek proverbs highlight traditional and family-centered values. These variations reflect the unique national mentality and socio-cultural experience of each culture. Conclusions: Proverbs reflect societal norms and values, with differences in interpretations depending on the culture. The study emphasizes the influence of cultural context in shaping these values and demonstrates the importance of proverbs in understanding different worldviews. Limitations: The study may be limited by the selected corpus of proverbs, and its conclusions might not fully represent the diversity of proverbs in each language. Contributions: This study contributes to comparative linguistics and linguacultural research, providing insights into how social values are represented in language, useful for intercultural language teaching.